2020
DOI: 10.1002/alz.043678
|View full text |Cite
|
Sign up to set email alerts
|

Safety monitoring in the U.S. study to Protect Brain Health Through Lifestyle Intervention to Reduce Risk (US POINTER)

Abstract: Background US POINTER is a multisite randomized clinical trial funded by the Alzheimer's Association. It is designed to evaluate whether different lifestyle interventions (exercise, nutrition, and cognitive and social stimulation) protect cognitive function over a 2‐year period in approximately 2000 older adults. Method We have designed a web‐based safety tracking system (STS) that meets the complexity of this trial that involves oversight of participants as they carry out the interventions by community partne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The nutrition intervention of AU‐ARROW is based on the MIND diet, which is a hybrid between the Mediterranean and the DASH diets that have shown beneficial effects on dementia risk 34 . The original FINGER trial 12 included a Mediterranean‐like diet (Healthy Nordic diet) and the US POINTER study 33 included the MIND diet, thus we again, aligned with US POINTER. Australia is a highly multicultural society, with more than one‐third of the population born overseas, as opposed to one in six in the United States being born overseas 35 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nutrition intervention of AU‐ARROW is based on the MIND diet, which is a hybrid between the Mediterranean and the DASH diets that have shown beneficial effects on dementia risk 34 . The original FINGER trial 12 included a Mediterranean‐like diet (Healthy Nordic diet) and the US POINTER study 33 included the MIND diet, thus we again, aligned with US POINTER. Australia is a highly multicultural society, with more than one‐third of the population born overseas, as opposed to one in six in the United States being born overseas 35 .…”
Section: Resultsmentioning
confidence: 99%
“…The FINGER inclusion criteria were used to include those with cognitive performance at the mean level or slightly lower than expected for age according to Finnish population norms. 12 US POINTER inclusion criteria were designed to identify at-risk individuals who may benefit most from a multimodal lifestyle intervention, 33 and AU-ARROW followed their design. Diet is associated with local factors, such as the availability of ingredients, cost, and cooking habits in a region.…”
Section: Harmonization Of the Study Protocolmentioning
confidence: 99%
“…Among 1,655 screened abstracts, we identified five completed and published dementia prevention trials with at least 500 community-dwelling persons: the Dose Responses to Exercise Training (DR's EXTRA) Study published in 2010 [20], the Finnish Geriatric Intervention Neuroepidemiology 2023;57:14-24 DOI: 10.1159/000528120 Study to Prevent Cognitive Impairment and Disability (FINGER) trial in 2015 [5], the Prevention of Dementia by Intensive Vascular care (preDIVA) trial in 2016 [4], the Multidomain Alzheimer Preventive Trial (MAPT) in 2017 [2], and the Healthy Ageing Through Internet Counselling in the Elderly (HATICE) trial in 2019. From grey literature and clinical trial registries, we additionally included another five trials that are ongoing at the time of the search: the US Study to Protect Brain Health Through Lifestyle Intervention to Reduce Risk (US-POINTER), a randomized controlled trial for Multimodal Intervention to Delay Dementia and Disability in China (MIND-CHI-NA), Maintain Your Brain-Trial (MYB), AgeWell.de, and the Japan-Multimodal Intervention Trial for Prevention of Dementia (J-Mint) [21][22][23][24][25]. A flowchart leading to the included studies is presented in online supplementary eFigure1.…”
Section: Resultsmentioning
confidence: 99%
“…Half of the dementia prevention trials that were included in this study were specifically designed to recruit a sample of persons at high risk of dementia based on the presence of cardiovascular risk factors [2,5,21,23,25]. Other trials used a more pragmatic design, with few inclusion criteria and enrolment based on age cut-offs, such as DR's EXTRA and preDIVA (also see online suppl.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that physical activity (PA) can slow cognitive decline 7–9 . Multidomain intervention study protocols involve strategies such as blood pressure control, promotion of PA, and management of other risk factors to assess their combined impact on reducing the risk of dementia 10–12 . Yet the optimal volume and intensity of PA required for this benefit remain unclear 8 .…”
Section: Introductionmentioning
confidence: 99%